Influence of ligand substitution and the solvent effect on the structures and magnetic properties of dinuclear Dy2 supramolecular architectures constructed with the bis-β-diketonate-Dy2 building block as a metalloligand. Issue 5 (12th January 2023) - Tang, Jiamin; Zhang, Sheng; Li, Linzhou; Yao, Linbin; Zhang, Ronghu; Yin, Bing; Zhang, Jiangwei
Abstract : Based on the bis-β-diketonate-Dy2 metalloligand, six dinuclear complexes with eight-coordinated geometries were synthesized solvothermally through different capping N-donor coligands or solvent systems. Abstract : Based on the bis-β-diketonate-Dy2 metalloligand [Dy2 (pbth)4 ]·2Et3 N (1, pbth = (3z, 3′z)-4, 4′-(1, 3-phenylene)bis(1, 1, 1-trifluoro-4-hydroxybut-3-en-2-one)), six dinuclear complexes with eight-coordinated geometries were synthesized solvothermally through different capping N-donor coligands or solvent systems. These complexes are namely [Dy2 (pbth)3 (Phen)2 ]·2C2 H5 OH (2 ), [Dy2 (pbth)3 (BPhen)2 ]·2C2 H5 OH (3 ), [Dy2 (pbth)3 (Dppz)2 ]·2C2 H5 OH (4 ), [Dy2 (pbth)3 (Dppz)2 ]·2CH3 OH (4a ), [Dy2 (pbth)3 (4-Dmbp)2 ]·CH3 OH·C2 H5 OH (5 ) and [Dy2 (pbth)3 (5-Dmbp)2 ]·CH3 OH (6 ) (Phen = 1, 10-phenanthroline, BPhen = 4, 7-diphenyl-1, 10-phenanthroline, dppz = dipyrido [3, 2- a :2′, 3′- c ] phenazine, 4-Dmbp = 4, 4′-dimethyl-2, 2′-bipyridyl, 5-Dmbp = 5, 5′-dimethyl-2, 2′-bipyridyl), respectively. In the synthetic processes of 2–6, one of four bis-β-diketonate ligands in the metalloligand is replaced by two capping N-donor coligands. The coordination geometries, metal distances and M–L–M torsion angles of the synthesized complexes are perceptibly fine-tuned by the modification of the capping N-donor coligands or the latticed solvent molecules. Systematic magnetic investigations indicate the different magnetic relaxation dynamics of 1–6 . Complex 1 displays no characteristics of single-molecule magnets (SMMs), while complexes 2–6 exhibit SMM behaviours in the absence of a static magnetic field. Complexes 2 and 3 possess effective energy barriers ( U eff ) of 110.18 (2) K and 133.21 (4) K, respectively. Theoretical analysis based on ab initio calculation provides some interpretations of experimental observation.